DIMENSI-DIMENSI SOSIAL DAN BUDAYA DALAM KERUSAKAN LINGKUNGAN, DAN PERUBAHAN IKLIM - Rusdi Syahra (Jurnal Masyarakat dan Budaya, 2012)
This article aims to discuss the extent to which social and cultural dimensions have been taken into account in the whole process of negotiations and agreements regarding the mitigation the impacts of and adaptation to climate change. Almost 18 years have passed since the establishment of Intergovernmental Panel on Climate Change (IPCC) in 1995, and 18 annual Conference of Parties (COP) have been held since then to set up agreements on the mitigation of climate change, but long and heated debates had taken place as to how to implement the agreements. It has been widely argued that social and cultural dimensions may have significant contribution in constraining the implementation of the agreements on the emission reduction of green house gasses (GSGs), especially when national interests have become a matter of non-negotiable. On the other hand some experts believe that social structures and cultural frameworks of individual countries could become the bases for concerted efforts by local communities to mitigate and adapt to climate change beyond the large scheme of the international agreements. Meanwhile Indonesia can play a strategic role in mitigating the impacts of global warming given the vast forest area at its disposal and can reap the benefits from carbon trading when land disputes with indigenous people and forest dependent communities could be settled. Keywords: environmental degradation, climate change, social dimension, cultural dimension, mitigation, adaptation, indigenous people